The Role of Bhabinkamtibmas in the Development of Siskamling to Prevent Curanmor Criminal Acts in Karawang Regional Police - Patria Nararya Vinutama (Advances in Police Science Research Journal, 2019)
This research is motivated by criminal acts of fraud in the jurisdiction of the Karawang Police Station which are still high and there is an increase every year. The increase in charter is an effort made in terms of prevention has not been implemented properly. The efforts of the police must be integrated with the community, especially in the implementation of social security systems. So that research is conducted which aims to find out the role of Bhabinkamtibmas in the guidance of social security, the factors that influence Bhabinkamtibmas and the efforts made by Bhabinkamtibmas in the guidance of social security. This research uses a qualitative approach, uses descriptive analysis research methods and uses data collection techniques in interviews, observations and document studies. Theories used by the author are Management theory from George R. Terry, Communication Theory from Haroid D. Lasswell, Management Theory from Harold Koontz and Cyrill O'Donnel and role concepts, Bhabinkamtibmas concepts, Siskamling Concepts and Curanmor Concepts. The results of the study found that the implementation of siskamling guidance had not gone well marked by the high number of criminal offenses, supporting factors in siskamling guidance that Bhabinkamtibmas had fulfilled in every village / kelurahan and there were books that supported Bhabinkamtibmas to conduct siskamling fostering in increasing community awareness of siskamling, inhibiting factors in siskamling development namely Bhabinkamtibmas is still charged in incidental and picket activities besides the budget provided does not meet the needs of Bhabinkamtibmas in conducting siskamling guidance as well as facilities and infrastructure that have not met the specified SOP. Based on the results of the study, the authors conclude that there is a need for a review of the procedures for Bhabinkamtibmas in guiding social security, vocational education is needed to support the ability of Bhabinkamtibmas, the need for facilities and infrastructure that supports and the need for funding funds provided to Bhabinkamtibmas in fostering social security.